Slavic Borrowings in the Ukrainian Folk Songs Texts (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the study of the Slavic borrowings of in the Ukrainian folk songs texts. The thematic groups of the borrowing lexics are indicated.
Keywords: borrowing; folk songs text; thematic group; lexics